Magnetically confined surface and bulk excitons in a layered antiferromagnet - Shao, Yinming; Dirnberger, Florian; Qiu, Siyuan; Acharya, Swagata; Terres, Sophia; Telford, Evan J; Pashov, Dimitar; Kim, Brian S Y; Ruta, Francesco L; Chica, Daniel G; Dismukes, Avalon H; Ziebel, Michael E; et al. (Nature materials, 2025)
The discovery of two-dimensional van der Waals magnets has greatly expanded our ability to create and control nanoscale quantum phases. A unique capability emerges when a two-dimensional magnet is also a semiconductor that features tightly bound excitons with large oscillator strengths that fundamentally determine the optical response and are tunable with magnetic fields. Here we report a previously unidentified type of optical excitation-a magnetic surface exciton-enabled by the antiferromagnetic spin correlations that confine excitons to the surface of CrSBr. Magnetic surface excitons exhibit stronger Coulomb attraction, leading to a higher binding energy than excitons confined in bulk layers, and profoundly alter the optical response of few-layer crystals. Distinct magnetic confinement of surface and bulk excitons is established by layer- and temperature-dependent exciton reflection spectroscopy and corroborated by ab initio many-body perturbation theory calculations. By quenching interlayer excitonic interactions, the antiferromagnetic order of CrSBr strictly confines the bound electron-hole pairs within the same layer, regardless of the total number of layers. Our work unveils unique confined excitons in a layered antiferromagnet, highlighting magnetic interactions as a vital approach for nanoscale quantum confinement, from few layers to the bulk limit.